The creative destruction of medicine : how the digital revolution will create better health care - Topol, Eric J., 1954- (Basic Books, 2012)
Until very recently, if you were to ask most doctors, they would tell you there were only two kinds of medicine: the quack kind, and the evidence-based kind. The former is baseless, and the latter based on the best information human effort could buy, with carefully controlled double-blind trials, hundreds of patients, and clear indicators of success. Well, Eric Topol isn't most doctors, and he suggests you entertain the notion of a third kind of medicine, one that will make the evidence-based state-of-the-art stuff look scarcely better than an alchemist trying to animate a homunculus in a jar.